An Exotic layered compound consisting of interconnected arsenato-polyoxovanadate clusters: thermal and magnetic properties and liquid phase exfoliation - Mahnke, Lisa K.; Stehlíková, Gabriela; Synnatschke, Kevin; Backes, Claudia; Näther, Christian; Bensch, Wolfgang (ChemNanoMat, 2021)
The compound [Mn(teta)]4V16As4O42(H2O)n ⋅ 10 H2O (teta=triethylenetetraamine) was synthesized under solvothermal conditions. The crystal structure consists of layers composed of V16As4O42 moieties joined by O−Mn−O bridges. The crystal water molecules can be thermally removed and they are reintegrated in humid atmosphere. The water sorption occurs in two steps indicating differing strengths of hydrogen bonding interactions. Investigations of the magnetic properties present evidence that the antiferromagnetic exchange interactions between the spins of the Mn2+ and of the V4+ cations are relatively strong. The magnetocaloric effect could be observed but is relatively small due to the antiferromagnetic exchange. Using liquid phase exfoliation, small crystallites with thicknesses as low as 10 nm could be obtained, while larger crystallites exhibit thicknesses of 20-40 nm.
Online veröffentlicht: 05 November 2020
Gesehen am 23.02.2024